(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The main interest of this research paper is to analyze through the cartoon and some press news the construction of the speech that was done by “Excelsior” and “El Día” related to women and their irruption in the first women international championships done in Italy (1970) and Mexico (1971). We took the idea that football became a conflict area for Mexican people that desired to practice this sport since they were generally defined as transgressors to the conditions and social values that should define them, and we ask about the role of the press in the elaboration of this vision. In this sense, we are specially interested in study the perspectives of the gender that press expressed, reproduced and projected around women, football and players from a triple connotation: as expression of shared ideas by the universe of their readers, as a diffusion channel of the speech of the dominating gender, and as a producer of imaginary collectives that finished up defining a particular perception of this sport and the appropriation by women of a reserved land, at least symbolically, to the expression of masculinity.